2019
DOI: 10.1111/1541-4337.12441
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Potential of Seaweed Polysaccharides: Structure, Bioactivity, Safety, and Toxicity

Abstract: In recent years, marine organisms including seaweeds have been highlighted as potential sources of useful metabolites and bioactive compounds, with vast biological and physiological activities. Seaweeds have long been used as a food source, for medicinal purposes, and as dietary supplements in various Asian countries, and their potential benefits have recently attracted the attention of many Western and European countries. Their commercial value depends on their applications in the food, nutraceutical, and pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
123
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(128 citation statements)
references
References 137 publications
(277 reference statements)
3
123
0
2
Order By: Relevance
“…Diatoms structural characteristics, and thus the different types of functional components have various biological applications. The fucoidan content varies in relation to seaweed species and season, although the content ranges from 20 to 200 g/kg DM, with the highest value in Fucus vesiculosus [17,30,31]. Laminarin, composed of (1,3)-b-D-glucopyranose residues, is the main reserve carbohydrate of brown seaweeds with a content ranging from 0 to 300 g/kg DM.…”
Section: Introductionmentioning
confidence: 99%
“…Diatoms structural characteristics, and thus the different types of functional components have various biological applications. The fucoidan content varies in relation to seaweed species and season, although the content ranges from 20 to 200 g/kg DM, with the highest value in Fucus vesiculosus [17,30,31]. Laminarin, composed of (1,3)-b-D-glucopyranose residues, is the main reserve carbohydrate of brown seaweeds with a content ranging from 0 to 300 g/kg DM.…”
Section: Introductionmentioning
confidence: 99%
“…Seaweeds have been used as a food source in various Asian countries since ancient times, and more recently have been explored for their nutraceutical potential (Tanna & Mishra, ). Seaweeds are a valid candidate to be considered as functional foods (De Quiros, Lage‐Yusty, & López‐Hernández, ), and demand is increasing in European and U.S. markets due to the benefits to nutrition and health and many consumer's preference for organic food (Tanna & Mishra, ). The global commercial seaweed market has been valued at U.S. $10.31 billion, and it is expected to reach U.S. $22.13 billion by 2024 (Grand View Research 2016), with a compound annual growth rate of 8.9% from 2016 to 2024 (Custódio, Villasante, Cremades, Calado, & Lillebø, ).…”
Section: Introductionmentioning
confidence: 99%
“…Seaweeds encounter various abiotic and biotic stresses due to fluctuating ocean conditions; therefore, they possess strong defense systems, and produce diverse secondary metabolites of pharmaceutical importance (Tanna & Mishra, ). Metabolites extracted from seaweeds have been explored as treatments for cancer, inflammation and oxidative stress, allergy, hypertension, lipidemia, obesity, and thrombosis, and they show antibacterial, antimicrobial, antiviral, antifungal, and other pharmacological properties (Tanna & Mishra, ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the good results presented by phlorotannins in in vivo studies, which showed their high pharmaceutical potential, there were some studies [31,44] where there was no information about the actual amount of compound administered, which hindered their comparison with other studies, as well as the reproducibility of the results. Also, the majority of the referenced studies, particularly those using a murine model, had a small group of individuals per study group (4)(5)(6), which may not be very representative of the real effect of the compounds. Future studies should increase the number of test subjects to increase the statistical power of the findings.…”
Section: Other Phlorotanninsmentioning
confidence: 99%
“…In the last few years, macroalgae attracted increasing attention from many industries of diverse branches such as fuel, plastics, cosmetics, pharmaceuticals, and food [1,2]. In fact, the chemical diversity within red (Rhodophyta), green (Chlorophyta), and brown (Phaeophyta) macroalgae offers the possibility of finding a wide variety of primary and secondary metabolites, with interesting properties and applications [1,[3][4][5][6][7]. Primary metabolites are directly involved in physiological functions, under normal growth conditions, such as reproduction, while secondary metabolites are mainly excretory products produced under different stress conditions, such as exposure to ultraviolet (UV) radiation, changes in temperature and salinity, or environmental pollutants.…”
Section: Introductionmentioning
confidence: 99%